Circular No. 28 from GC to Secretaries of all affiliated trade unions, 4 May 1926, re: Mining Dispute (page 1)
1926-05-04 "Circular No. 28 from GC to Secretaries of all affiliated trade unions, 4 May 1926, re: Mining Dispute (page 1)" [g0700001.jpg], 4 May 1926 TUC Organisation